Oracle weblogic server 12c administration handbook - Alapati, Sam R. (New Delhi McGraw Hill Education, 2014)
"Maintain a high-performance enterprise application framework using the detailed information in this authoritative resource. Through expert instruction and real-world examples, Oracle WebLogic Server 12c Administration Handbook fully explains the latest management tools and techniques. Learn how to work from the Oracle WebLogic Server Administration Console or command line, configure servers and clusters, deploy applications, and optimize application performance. Tuning, troubleshooting, and load balancing are thoroughly covered in this Oracle Press guide"-- |c Provided by publisher
Machine generated contents note: 1. Installing WebLogic Server and using the Management Tools -- 2.Administering WebLogic Server Instances -- 3.Creating and Configuring WebLogic Server Domains -- 4.Configuring Naming, Connections, Transactions, and Messaging -- 5.Configuring the WebLogic Server Environment -- 6.Monitoring and Troubleshooting WebLogic Server -- 7.Working with WebLogic Server Clusters -- 8.Understanding WebLogic Server Application Deployment -- 9.Managing WebLogic Server Security -- 10.WebLogic Server Performance Tuning -- 11.Middleware management with Enterprise Manager 12c Cloud Control -- 12.WebLogic Performance Monitoring and JVM Tuning Index.
Includes index
Keywords: Web servers; Client/server computing